Hofmeister‐Effect‐Guided Ionohydrogel Design as Printable Bioelectronic Devices. Issue 30 (21st June 2020) - Shang, Yinghui; Wu, Chu; Hang, Chengzhou; Lu, Hongliang; Wang, Qigang
Abstract: Bioelectronic platforms convert biological signals into electrical signals by utilizing biocatalysts that provide tools to monitor the activity of cells and tissues. Traditional conducting materials such as solid conductors and conducting polymers are confronted with a great challenge in sophisticated production processes and mismatch at biological tissues–machine interfaces. Furthermore, the biocatalyst, the key functional component in the electron‐transfer reaction for bio‐signal detection denatures easily in an ionic conductive solution. Herein, a bionic strategy is elaborately developed to synthesize an ionohydrogel bioelectronic platform that possesses extracellular‐matrix‐like habitat by employing hydrated ionic liquids (HILs) as ionic solvent and bioprotectant. This strategy realizes an integration of ionic and enzymatic electronic circuits and minimization of the disparities between tissues and artificial machines. The Hofmeister effect of HILs on enzyme proteins and polymer chains ensures the high bioactivity of the enzymes and greatly improves the mechanical properties of the ionohydrogels. Moreover, hydrogen bonds formed by ILs, water, and polymer chains greatly improve the water‐retention of the ionohydrogel and give it more practical significance. Consequently, the promising ionohydrogel is partly printed and fabricated into wearable devices as a pain‐free humoral components monitor and a wireless motion‐sensor. Abstract : Transducing biosignals imperatively needs a hybrid circuit of mobile ions and electrons. An ionohydrogel bioelectronic platform is developed via enzymatic polymerization in hydrated ionic liquids, realizing the integration of ionic and enzymatic electronic circuits. The platform ensures the high bioactivity of enzymes and favorable ionic conductivity that are integrated into an easy‐to‐use glucose sensor and a wireless human‐motion monitor and energy‐storage device.